The potential of using low oxygen and ethyl formate or ethyl acetate to disinfest fresh fruit in storage - Jamieson, L.E.; Page-Weir, N.E.M.; Chhagan, A.; Connolly, P.G.; Poulton, J.; Kean, A.M. (New Zealand Plant Protection, 2013)
Low oxygen and/or generally recognised as safe (GRAS)/food additive (FA) treatments in combination with cool storage have the potential to disinfest a range of commodities of various pests This paper reports on research to determine the tolerance of second/third and fifth instar codling moth larvae fifth instar lightbrown apple moth larvae mixed stages of greedy scale and obscure mealybugs and diapausing twospotted mite adults to ultra low oxygen (ULO lt;05 O2) and ULO combined with two GRAS/ FA compounds ethyl acetate and ethyl formate ULO alone did not consistently enhance mortality of these pests compared with air cool storage However addition of 30005000 ppm of ethyl acetate or ethyl formate reduced the time taken to achieve 99 mortality from weeks or months to between 8 h and 5 days depending on the pest